Prevalence of Piriformis Muscle Tightness among Undergraduate Medical Students - Atta Muhammad, Muhammad Rizwan Rana, Tooba Amin, Christina Angela, Felicianus Anthony Pereira, Mazhar Ali Bhutto (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the prevalence of piriformis muscle tightness among allied health students, and its relationship with age, gender and year of study. Methods: A cross sectional study was conducted. A sample size of 259 was calculated using Open Epi v3.01. Allied health students from physical therapy, occupational therapy and prosthetics & orthotics programs participated in this study, which lasted 4 months. After obtaining informed consent, data was collected through a self-developed questionnaire. Piriformis muscle tightness, and symptom recurrence, was determined using the FAIR test. Results: Average age of participants was 21.94±1.81 years. Females comprised of 79.9% of the study population. High percentage (85.3%) were from the physical therapy program. Most common posture was crossed leg sitting (48.3%). Positive FAIR test was found in 41.7% of the population. Strong correlation between age-group with FAIR test was noted (p=0.036). Conclusion: Piriformis muscle tightness is prevalent in those who engage in prolonged sitting postures. Furthermore, strong association of piriformis tightness with age is present, whereas no relationship with gender and year of study has been observed.